Can findings from randomized controlled trials of social skills training in autism spectrum disorder be generalized?: the neglected dimension of external validity - Jonsson, Ulf; Choque-Olsson, Nora; Bölte, Sven (Autism, 2016)
Systematic reviews have traditionally focused on internal validity, while external validity often has been overlooked. In this study, we systematically reviewed determinants of external validity in the accumulated randomized controlled trials of social skills group interventions for children and adolescents with autism spectrum disorder. We extracted data clustered into six overarching themes: source population, included population, context, treatment provider, treatment intervention, and outcome. A total of 15 eligible randomized controlled trials were identified. The eligible population was typically limited to high-functioning school-aged children with autism spectrum disorder, and the included population was predominantly male and Caucasian. Scant information about the recruitment of participants was provided, and details about treatment providers and settings were sparse. It was not evident from the trials to what extent acquired social skills were enacted in everyday life and maintained over time. We conclude that the generalizability of the accumulated evidence is unclear and that the determinants of external validity are often inadequately reported. At this point, more effectiveness-oriented randomized controlled trials of equally high internal and external validity are needed. More attention to the determinants of external validity is warranted when this new generation of randomized controlled trials are planned and reported. We provide a tentative checklist for this purpose.